Some Algebraic structures of Complex Fermatean Fuzzy Subgroups (European Journal of Pure and Applied Mathematics, 2025)
A complex Fermatean fuzzy set provides a detailed framework for representing a specific type of information and has been effectively applied to decision-making problems. This study introduces complex Fermatean fuzzy subgroups (CFFSGs), an extension of Fermatean fuzzy subgroups, and complex Pythagorean fuzzy subgroups. The key innovation of CFFSGs lies in their capacity to represent two variables within their algebraic structure, surpassing the capabilities of traditional Fermatean fuzzy subgroups. The research establishes the formal definition and properties of CFFSGs, adapting them to a complex framework that incorporates amplitude and phase components. Additionally, the concepts of complex Fermatean fuzzy cosets and complex Fer-matean fuzzy normal subgroups are introduced. The study also investigates and examines the characteristics of homomorphisms between complex Fermatean fuzzy subgroups.
Keywords: Complex fermatean fuzzy subgroup; complex fermatean fuzzy coset; complex fermatean fuzzy normal subgroup; homomorphism of fermatean fuzzy subgroup